Development of 5E Inquiry-Based Learning Activities Integrated with Board Games in History for Grade 6 Students - Chuamram, Pimlapat; Polyiem, Thitiworada (ARU Research Journal Humanities and Social Sciences, 2026)
This research aimed 1) to develop an effective 5E inquiry-based learning activity combined with a board game for sixth-grade history students, meeting the 80/80 effectiveness criterion;to 2) compare students’ analytical thinking abilities in history before and after the implementation of the 5E inquiry-based learning activity combined with a board game; and 3) to study students’ satisfaction with the 5E inquiry-based learning activity combined with a board game. The sample consisted of 24 sixth-grade students from Ban Lao (Kuruprachanukroh) School, Semester 2, academic year 2025, selected using cluster random sampling. The research design was a single-group experimental design with pre- and post-test measurements. The research instruments included: 1) ten inquiry-based learning activity plans (5E model) combined with board games, totaling 10 hours; 2) a 30-item multiple-choice test with four options measuring analytical thinking skills; and 3) a 15-item five-level Likert scale satisfaction questionnaire. Data were analyzed using percentages, mean, standard deviation, and a paired-samples t-test. The research findings revealed that: 1) The 5E inquiry-based learning activity combined with a board game in history had process efficiency (E1) and outcome efficiency (E2) of 85.78/85.28, exceeding the set criterion of 80/80; 2) The analytical thinking ability in history of sixth-grade students was significantly higher after the intervention than before, at a statistical significance level of .05, with an average pre-intervention score of 18.75 and a post-intervention score of 25.75; and 3) Students expressed the highest level of satisfaction with the 5E inquiry-based learning activity combined with the board game.